Ergonomic Risk Factors And Musculoskeletal Disorders Among Cashier Workers - Nur Afiqah Alya, Zahari (2025)
Ergonomic risk factors and musculoskeletal disorders (MSDs) are a critical occupational health issue among retail cashiers due to prolonged standing, repetitive movements, and awkward postures. This study aimed to examine the correlations between ergonomic risk factors and musculoskeletal discomfort among cashiers working in three hypermarkets in Kelantan. A cross-sectional study was conducted using the Nordic Body Map Questionnaire and Rapid Entire Body Assessment (REBA). A total of 44 cashiers, selected through proportionate stratified sampling, participated in the study. The findings revealed significant correlations between REBA scores and pain in specific body regions, including the lower back (r = 0.341, p = 0.024), left upper arm (r = 0.301, p = 0.047), and right foot (r = 0.334, p = 0.027). Repetitive tasks, prolonged standing, and improper workstation setups were identified as key contributors to MSDs. These results highlight the need for ergonomic interventions, such as adjustable workstations, regular breaks, and ergonomic training programs, to mitigate the risk of MSDs among cashiers. In conclusion, this study emphasizes the importance of proactive measures to reduce ergonomic risks in the retail sector. The findings provide valuable insights for employers and hypermarket organizations to enhance workplace safety and improve employee well-being in retail environments.